2015
DOI: 10.1007/978-3-662-47241-5_43
|View full text |Cite
|
Sign up to set email alerts
|

The Research of E-Commerce Enterprises’ Price Game: Empirical Studies in China

Abstract: With the rapid development of Internet in China, network economy, especially e-commerce enterprises, plays an increasingly important role in the overall situation of economy. However, excessive and vicious competition among enterprises in the network market occurs frequently, resulting in tremendous waste of resources, lack of fairness and some other consequences. Through focusing on the some typical B2C and O2O cases in China, this paper analyzes the competition behavior and strategy choices of e-commerce ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Furthermore, interviews with customers revealed that many questioned the quality of the products offered by the fresh food e-commerce platforms, which confirms their previous negative experiences with other e-commerce businesses. Thus, despite the number of transactions continues to rise, most Chinese e-commerce firms are involved in price wars, pursuing impractical business models, and running at a loss (Huang et al, 2015;Zhao, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interviews with customers revealed that many questioned the quality of the products offered by the fresh food e-commerce platforms, which confirms their previous negative experiences with other e-commerce businesses. Thus, despite the number of transactions continues to rise, most Chinese e-commerce firms are involved in price wars, pursuing impractical business models, and running at a loss (Huang et al, 2015;Zhao, 2017).…”
Section: Introductionmentioning
confidence: 99%